RELATIONS SONOGRAPHIC PARAMETERS OF LIVER, PANCREAS AND GALL BLADDER WITH BODY SIZES IN PRACTICALLY HEALTHY URBAN WOMEN OF PODILLYA - Гунас, І.В.; Прокопенко, С.В.; Мельник, М.П. (World of Medicine and Biology, 2016)
In 154 practically healthy women of Podillya of the first adulthood in general and in the distribution on age groups (under 25 and over 25) conducted a qualitative and quantitative analysis of the relationship of sonographic parameters of liver and its blood vessels, pancreas and gallbladder with anthropo-somatotypological indicators. It was established that the vast majority of correlations in women overall group and in the allocation on age groups are straight. Identified age characteristics of relations between groups sonographic parameters of the abdomen and anthropo-somatotypological performance.